An experimental study on the cutting failure of polymer grouting. (20th October 2020) - Lin, Zhenzhen; Guo, Chengchao; Cao, Dingfeng; Ni, Pengpeng; Wang, Fuming
Abstract: The technique of polymer grouting is frequently used in underground projects. The life span of the grouted body needs to be evaluated carefully to guarantee the long-term performance of trenchless repair by polymer grouting. Cutting failure of grouting polymer by rock or soil under water pressures can occur to affect the plugging effect. In this study, the mechanism of cutting failure in polymers with different densities is systematically investigated, where the effects of cutting depth and cutting-edge radius are assessed. Phase–space reconstruction for chaotic time series and trend analysis are conducted to analyze the experimental data to understand the fluctuation nature of cutting force on polymer. It is found that the passive cutting force on polymer first increases until it reaches a transition point, after which it decreases, along with the occurrence of broken chips. The observed cutting mechanism can affect the service life of polymer grouting significantly. Critical parameters that can influence the cutting force are then determined, based on which a prediction model is proposed for selecting and optimizing the polymer grouting material in practice.